2010
DOI: 10.1073/pnas.1000284107
|View full text |Cite
|
Sign up to set email alerts
|

Signal-dependent turnover of the bacterial flagellar switch protein FliM

Abstract: Most biological processes are performed by multiprotein complexes. Traditionally described as static entities, evidence is now emerging that their components can be highly dynamic, exchanging constantly with cellular pools. The bacterial flagellar motor contains ∼13 different proteins and provides an ideal system to study functional molecular complexes. It is powered by transmembrane ion flux through a ring of stator complexes that push on a central rotor. The Escherichia coli motor switches direction stochast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
181
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(202 citation statements)
references
References 29 publications
(45 reference statements)
12
181
1
Order By: Relevance
“…2A shows the motor of a cell expressing a large amount of CheY that recovered nearly all of its initial fluorescence intensity after 20 min, due to continuous replacement of photobleached FliM molecules with unbleached molecules. Previous experiments over similar timescales have ruled out synthesis of new fluorescent molecules as reasons for exchange (13). We carried out similar experiments with cells deleted for cheY that rotated exclusively CCW.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…2A shows the motor of a cell expressing a large amount of CheY that recovered nearly all of its initial fluorescence intensity after 20 min, due to continuous replacement of photobleached FliM molecules with unbleached molecules. Previous experiments over similar timescales have ruled out synthesis of new fluorescent molecules as reasons for exchange (13). We carried out similar experiments with cells deleted for cheY that rotated exclusively CCW.…”
Section: Resultsmentioning
confidence: 93%
“…Fluorescence recovery after photobleaching (FRAP) experiments have shown that FliM molecules in the C-ring continuously exchange with a pool of FliM molecules present elsewhere in the cell body, provided that the cells contain active CheY (13)(14)(15). The dependence on CheY was not understood (16).…”
Section: Resultsmentioning
confidence: 99%
“…Such analytical methods may also be employed for studies involving fluorescence recovery after photobleaching (FRAP) and fluorescence loss in photbleaching (FLIP) at single cell level and single molecule complex level to quantify the extent of dynamic molecular turnover. 17,18 …”
Section: Counting Molecules In Fluorescently-labelled Complexes To Qumentioning
confidence: 99%
“…35 There is common agreement on a canonical shape for E. coli bacteria, namely that of a cylindrical body capped by hemispheres, with a typical diameter width of ~1 m and endto-end length in the range ~2-5 m, depending primarily on stage in the cell cycle. 7,8,[16][17][18] Here, we define a local coordinate system from each bacterium's position, orientation, length and width, as estimated from the non-fluorescence brightfield imaging data. Through observations using light microscopy we can characterize the size and shape of each detected E. coli cell individually, with its characteristic 'stubby' object shape 32 shown in Fig.…”
Section: Automated Segmentation Of Cellular Images From Light Microscopymentioning
confidence: 99%
See 1 more Smart Citation